The efficacy of droperidol, metoclopramide, propofol, and ondansetron for the prevention of nausea and vomiting following middle ear surgery - Karlidag, Turgut; Kaygusuz, Irfan; Bestaş, Azize; Keleş, Erol; Demirbag, Erhan; Yalçin, Sinasi (My University, 2002)
OBJECTIVES: The efficacy and reliability of prophylactic antiemetic therapy with low dose propofol, droperidol, metoclopramide, and ondansetron were evaluated in a randomized, double-blind, and prospective design. PATIENTS AND METHODS: A total of 101 ASA I-II patients (34 females, 67 males; age range 16 to 53 years) undergoing middle ear surgery for chronic otitis media or its sequelae were randomly assigned to receive prophylactic antiemetic therapy with propofol (n=21, 0.5 mg/kg), droperidol (n=19, 20 mg/kg), metoclopramide (n=23, 0.2 mg/kg), ondansetron (n=21, 4 mg), and placebo (n=20, 0.9% NaCl). All drugs were administered intravenously five minutes before extubation. RESULTS: In the early postoperative period (0 to 3 hours), the percentages of patients free from nausea and vomiting were 100% with droperidol, 71.4% with ondansetron and propofol, 52.1% with metoclopramide, and 35% with placebo. Ondansetron (90.4%) was found the most effective to prevent and control nausea and vomiting during the postoperative 3 to 24 hours, followed by droperidol (84.2%), propofol (57.1%), metoclopramide (47.8%), and placebo (40%). Compared with controls, the number of patients without nausea and vomiting was significantly greater in each treatment group but metoclopramide (p<0.05). No significant differences were detected with respect to adverse effects. CONCLUSION: Droperidol and ondansetron seem to exert the highest efficacy to prevent nausea and vomiting during the postoperative 0 to 3 hours and 3 to 24 hours, respectively.
Orta kulak cerrahisi sonrasinda oluşan bulanti ve kusmada droperidol, metoklopramid, propofol ve ondansetronun etkinligi.
Keywords: Adolescent; Adult; Antiemetics; Chronic Disease; Double-Blind Method; Droperidol; Female; Humans; Infusions, Intravenous; Intraoperative Period; Male; Metoclopramide; Middle Aged; Ondansetron; Otitis Media; Postoperative Nausea and Vomiting; Propofol; Prospective Studies; Treatment Outcome; antiemetic agent; droperidol; metoclopramide; ondansetron; propofol; adolescent; adult; article; chronic disease; clinical trial; controlled clinical trial; controlled study; double blind procedure; female; human; intraoperative period; intravenous drug administration; male; middle aged; otitis media; postoperative nausea and vomiting; prospective study; randomized controlled trial; treatment outcome